Remotely Sensed Deformation and Thermal Anomalies at Mount Pagan, Mariana Islands - Henderson, Scott T.; Pritchard, Matthew E.; Cooper, Jennifer R.; Aoki, Yosuke (Frontiers in Earth Science, 2019)
Mt Pagan is an active volcano in the Mariana Island Arc, having produced a large eruption (>0.1 km3) in 1981, and recent smaller eruptions (>0.001 km3) in2011 and 2012. In this study we examine available Interferometric Synthetic Aperture Radar(InSAR) from Envisat and ALOS between October 2004 and June 2010 for precursory deformationleading up to the most recent eruptions. Although we do not observe evidence for shallowmagma reservoir inflation, we do observe a zone of subsidence of up to -3 cm/yr located onthe northern flank likely caused by continuing scoria compaction of 1981 eruptive deposits.CosmoSkyMed InSAR data spanning the October 2012 eruption also shows deposit subsidence,but no detectable co-eruptive deflation. We also present remotely-sensed thermal time series fromthe MODIS and ASTER instruments spanning over a decade. There are two distinct locationsof anomalous surface temperatures on the island, which correlate with previously documented,fumarolically active vents at South Pagan and Mt. Pagan. While elevated temperatures duringthe eruptions are visible from space in both ASTER and MODIS data, we find no clear thermalprecursors before eruption. The available data may have had insufficient spatial and temporalresolution to detect either deformation or thermal precursors if the magmatic system had rapidtransitions between quiescence and eruption. Looking ahead, satellite sensors with improvedspatial and temporal resolution will help characterize transient dynamics at small and remotevolcanic islands such as Pagan.